1994
DOI: 10.1007/bf00365733
|View full text |Cite
|
Sign up to set email alerts
|

Amikacin and ceftazidime as empirical antibiotic therapy in severely neutropenic patients: analysis of prognostic factors

Abstract: This study aimed to evaluate the efficacy of amikacine and ceftazidime as an empirical antibiotic therapy for neutropenic patients affected by haematological neoplasms and to investigate the presence of prognostic features suggesting a poor outcome with this antibiotic combination at the onset of infection. This could allow the identification of subgroups of patients with a low rate of response to amikacin/ceftazidime therapy; in these patients different initial empirical therapy may be indicated. The study po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The derivation and validation of both models involved heterogeneous samples, with solid tumours, acute leukaemia and bone marrow transplantation (BMT), which differ in their baseline characteristics. Therefore, FN is managed differently in each particular scenario (Rossini et al , 1994; Nakagawa et al , 2009). …”
mentioning
confidence: 99%
“…The derivation and validation of both models involved heterogeneous samples, with solid tumours, acute leukaemia and bone marrow transplantation (BMT), which differ in their baseline characteristics. Therefore, FN is managed differently in each particular scenario (Rossini et al , 1994; Nakagawa et al , 2009). …”
mentioning
confidence: 99%
“…Febrile neutropenia after chemotherapy for hematologic malignancies remains a frequent and potentially life‐threatening complication, although the mortality rate associated with this complication has decreased to less than 10% over the last 3 decades 1. Nonetheless, several studies have demonstrated that patients with neutropenia are a heterogeneous group exhibiting variability in terms of risk of infection‐related morbidity and mortality 2–8. At present, low‐risk patients with febrile neutropenia are safely managed with oral antibiotics9, 10 or with early discharge from hospital on the basis of suitable risk models 6, 8, 11…”
mentioning
confidence: 99%
“…1,2 A number of prognostic factors have been identified, the most important of which C are the type and stage of the underlying disease and the aggressiveness of cytotoxic chemotherapy. [3][4][5][6][7][8][9][10][11] Both factors have a strong influence on the duration and severity of granulocytopenia. As compared with patients who have granulocytopenia for an extended time, those in whom the duration of granulocytopenia is short may be at lower risk for infectious complications, are more likely to have a response to empirical antimicrobial therapy, and may require a different approach to the management of fever.…”
mentioning
confidence: 99%